2021
DOI: 10.1371/journal.pone.0260753
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal levels of human beta defensins during bacterial vaginosis

Abstract: Aims To compare the cervicovaginal levels of human beta defensin (hBD)-1, 2 and 3 of women according to the status of Nugent-defined bacterial vaginosis (BV). Methods A total of 634 women of reproductive age were included in the study. Participants were equally distributed in two groups: according to the classification of vaginal smears according to Nugent criteria in normal (scores 0 to 3) and BV (scores ≥7). Cervicovaginal fluid samples were used for measurements of hBDs1, 2 and 3 levels by enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Several recent studies have demonstrated an association between low levels of β-defensin-2 and numerous obstetric and gynecologic pathologies, including preterm birth, bacterial vaginosis, lichen sclerosis, sexually transmitted infections. 3,12,28,29 In regards to GBS specifically, prior in vitro work by Castro-Leyva et al demonstrated that when incubated with S. agalactiae, choriodecidual cells increased production of β-defensin-2. 30 Boldenow et al showed increased β-defensin-2 production by GBS-exposed amnion cells and also found that in bacterial culture, β-defensin-2 decreased GBS viability in a concentration-dependent manner.…”
Section: Results In the Setting Of What Is Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated an association between low levels of β-defensin-2 and numerous obstetric and gynecologic pathologies, including preterm birth, bacterial vaginosis, lichen sclerosis, sexually transmitted infections. 3,12,28,29 In regards to GBS specifically, prior in vitro work by Castro-Leyva et al demonstrated that when incubated with S. agalactiae, choriodecidual cells increased production of β-defensin-2. 30 Boldenow et al showed increased β-defensin-2 production by GBS-exposed amnion cells and also found that in bacterial culture, β-defensin-2 decreased GBS viability in a concentration-dependent manner.…”
Section: Results In the Setting Of What Is Knownmentioning
confidence: 99%
“…7,8 Furthermore, recent works have demonstrated that antimicrobial peptide β-defensin-2 is associated with nonoptimal CV microbiota as well as bacterial vaginosis and sexually transmitted infections, but the impact of β-defensin-2 on GBS colonization in pregnancy has not yet been examined. 3,5,12,13 Therefore, we sought to determine whether the CV microbiota was associated with GBS RV colonization in pregnancy. We examined the relationship between GBS RV colonization and various characteristics of the CV microbiome at multiple time points throughout pregnancy.…”
mentioning
confidence: 99%
“…Clinical studies have found defensin deficiency in vaginal lavage fluids of women with BV. Effective treatment normalizes defensin levels in BV, suggesting that abnormal defensin levels are a consequence of G. vaginalis infection ( Balu et al , 2002 ; Valore et al , 2006 ; Fan et al , 2008 ; Libby et al , 2008 ; Xu et al , 2008 ; Mitchell et al , 2013 ; Noda-Nicolau et al , 2021 ). However, in vitro experiments showed that G. vaginalis infection could induce HBD1–3 secretion in human chorioamnion ( Zaga-Clavellina et al , 2012a ).…”
Section: Host Defence By Defensins In the Reproductive Systemmentioning
confidence: 99%
“…Inconsistent changes in defensin levels were found in lavage fluids from patients with G. vaginalis infection, for instance, decreased levels of HBD1–3 in the cervix of childbearing age women ( Noda-Nicolau et al , 2021 ), increased HNP1–3 concentrations in vaginal fluid of pregnant women ( Balu et al , 2002 ; Xu et al , 2008 ) and low HBD3 concentrations in vaginal fluid of African American pregnant women ( Mitchell et al , 2013 ). In postmenopausal women, HBD1 levels were significantly decreased, and HBD2 and HBD3 levels were significantly increased ( Brunner et al , 2021 ).…”
Section: Host Defence By Defensins In the Reproductive Systemmentioning
confidence: 99%